Cardiovascular activity of the chiral xanthone derivatives. Issue 20 (15th October 2015) - Szkaradek, Natalia; Rapacz, Anna; Pytka, Karolina; Filipek, Barbara; Żelaszczyk, Dorota; Szafrański, Przemysław; Słoczyńska, Karolina; Marona, Henryk
Graphical abstract: Abstract: A series of 6 derivatives of xanthone were synthesized and evaluated for cardiovascular activity. The following pharmacological experiments were conducted: the binding affinity for adrenoceptors, the influence on the normal electrocardiogram, the effect on the arterial blood pressure, the effect on blood pressor response and prophylactic antiarrhythmic activity in adrenaline induced model of arrhythmia (rats, iv). Two compounds revealed nanomolar affinity for α1 -adrenoceptor which was correlated with the strongest cardiovascular (antiarrhythmic and hypotensive) activity in animals' models. They were enantiomers of previously described ( R, S )-4-(2-hydroxy-3-(4-(2-methoxyphenyl)piperazin-1-yl)propoxy)-9 H -xanthen-9-one hydrochloride and revealed similar antiarrhythmic potential in adrenaline induced model of arrhythmia in rats after intravenous injection (ED50  = 0.53 mg/kg and 0.81 mg/kg, respectively). These values were lower than values obtained for reference drug urapidil. These compounds were more active in this experiment than urapidil (ED50  = 1.26 mg/kg). The compound5 administered iv at doses of 0.62–2.5 mg/kg at the peak of arrhythmia prevented and/or reduced the number of premature ventricular beats in a statistically significant manner. The ED50 value was 1.20 mg/kg. The S -enantiomer (6 ) given at the same doses did not show therapeutic antiarrhythmic activity in this model. These compounds significantly decreased the systolic and diastolic blood pressure throughout the whole observation period in anesthetized, normotensive rats. The studied enantiomers showed higher toxicity than urapidil, but imperceptibly higher that another cardiovascular drugs, that is, carvedilol or propranolol. They were also evaluated for mutagenic potential in the Ames ( Salmonella ) test. It was found that at the concentrations tested the compounds were non mutagenic when compared to solvent control. Results were quite promising and suggested that in the group of xanthone derivatives new potential antiarrhythmics and hypotensives might be found.